Multiple meanings of money how women see microfinance - Premchander, Smita; Prameela, V.; Chidambaranathan, M.; Jeyaseelan, L.; Sage eBooks (New Delhi ; London : SAGE, 2009)
This book analyses what microfinance money means to women; and in doing so, it focuses on the perspectives of individual women and of women-only groups. It explores women's own money management strategies, group dynamics and learning processes in groups, and in this context, discusses the divergence between the perspectives of external intervening agencies, and those of women who are members of self-help groups.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Microfinance -- India; Women -- India -- Economic conditions; Economic assistance, Domestic -- India; Women in economic development -- India; Electronic books